IMPLEMETASI MANAJEMEN PENGETAHUAN SEBAGAI UPAYA PENGEMBANGAN LEMBAGA PENDIDIKAN UNGGUL PADA TK. WIDYA NUGRAHA BATUBULAN - I Nyoman Bagus Suweta Nugraha; Ketut Agustini; I Wayan Sukra Warpala; I Gde Wawan Sudatha (Widyadari : Jurnal Pendidikan, 2022)
Along with the development and advancement of technology, the competition that occurs requires people to follow the flow of adjustment as well as the world of education which now provides many alternative choices and levels of quality. Educational institutions need to develop excellence in order to survive, compete and maintain the continuity of the institution properly. The resources needed to maintain the continuity of the institution are not solely from traditional resources but also must be from intangible resources, namely knowledge. To benefit from the knowledge possessed and what knowledge must be possessed, educational institutions must manage their knowledge through knowledge management. Educational institutions must consciously know the knowledge they have and their benefits to improve performance and increase innovation and creativity. To achieve superior educational institutions, knowledge management is needed, namely the ability to create and maintain value that is greater than the competitiveness of the core institution. Knowledge and experience are able to create, communicate and apply knowledge about various things to achieve organizational goals, namely to become a superior educational institution.